36.8k views
2 votes
(2-5√8)(4-6√3)
I need help​

User Jocull
by
4.4k points

1 Answer

3 votes

Answer:

see explanation

Explanation:

Using the rule of radicals


√(a) ×
√(b)
√(ab)

Given

(2 - 5
√(8) )(4 - 6
√(3) )

Each term in the second factor is multiplied by each term in the first factor, that is

2(4 - 6
√(3) ) - 5
√(8)(4 - 6
√(3) ) ← distribute both parenthesis

= 8 - 12
√(3) - 20
√(8) + 30
√(24) → *

Simplify
√(8) and
√(24)


√(8) =
√(4(2)) =
√(4) ×
√(2) = 2
√(2)


√(24) =
√(4(6)) =
√(4) ×
√(6) = 2
√(6)

Back to *

= 8 - 12
√(3) - 20(2
√(2) ) + 30(2
√(6) )

= 8 - 12
√(3) - 40
√(2) + 60
√(6)

User Iandisme
by
4.7k points